2021
DOI: 10.1177/23821205211020758
|View full text |Cite
|
Sign up to set email alerts
|

Flourishing as a Measure of Global Well-being in First Year Residents: A Pilot Longitudinal Cohort Study

Abstract: Background: Physician well-being is critical to optimal learning and performance, yet we remain without validated measures to gauge the efficacy of well-being curricula for trainees. This study evaluates initial evidence of flourishing as a valid measure of global well-being in postgraduate-year-1 residents (PGY-1s), providing a means of assessing well-being intervention efficacy. Study design: In this single-site study of PGY-1s participating in Enhanced Stress Resilience Training (ESRT), an online questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…Interestingly, to our knowledge, the only other study to examine flourishing using an alternative measure found results that are discrepant with those found here and with the other studies that used the MHC-SF. Specifically, this study and the previous two that used the MHC-SF found higher rates of flourishing among residents than has been found in a general adult population [ 73 , 85 ]. However, the study that used VanderWeele’s flourishing measure found lower flourishing scores, prompting the interpretation that medical residents have lower rates of flourishing than community samples [ 112 ].…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Interestingly, to our knowledge, the only other study to examine flourishing using an alternative measure found results that are discrepant with those found here and with the other studies that used the MHC-SF. Specifically, this study and the previous two that used the MHC-SF found higher rates of flourishing among residents than has been found in a general adult population [ 73 , 85 ]. However, the study that used VanderWeele’s flourishing measure found lower flourishing scores, prompting the interpretation that medical residents have lower rates of flourishing than community samples [ 112 ].…”
Section: Discussionsupporting
confidence: 53%
“…For example, an early study of over 3000 adults in the United States between the ages of 25 and 74 revealed that only 17% fit the criteria for flourishing, with 12% of adults meeting the criteria for languishing [ 62 ]. Lebares and colleagues’ longitudinal survey of mixed-specialty first year trainees found rates of flourishing between 76% to almost 86%, depending on when the resident was surveyed [ 73 ]. In combination, the findings from our study and those from the study of Lebares et al indicate that flourishing remains high among resident physicians, even while burnout and depression rates are of concern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several reasons why mindfulness-attentional focus on the present, momentary, experience, and regulation of emotions in the present moment via a nonjudgmental attitude [68]-emerges as salient in discourse related to wisdom and flourishing. First, correlations between high levels of wisdom and mindfulness [69] have been noted, and mindfulness has been identified as a predictor of wisdom [70,71]; second, mindfulness has also been correlated with human flourishing [72][73][74] and lower allostatic load [75]. Thirdly, in an era where the need for wise leaders is an urgent priority, it is worth noting the emerging research demonstrating that mindfulness among leaders in various workplaces has a positive influence on employee wellbeing [76][77][78][79].…”
Section: Can We Boost Wisdom Flourishing?mentioning
confidence: 99%